Development of Microlearning Modules based on Candi Singasari as a Culturally Responsive Teaching to Enhance Problem-Solving Ability - Utami, Wikan Budi; Setyosari, Punaji; Sa'dijah, Cholis; Praherdhiono, Henry (JTP - Jurnal Teknologi Pendidikan, 2024)
The aim of this research is to find out how the implementation of the development of a microlearning module containing Culturally Responsive Teaching at Candi Singasari can improve students' problem solving abilities. The development model in this study refers to the ADDIE development model. The study involved one media expert, one material expert, and the research subjects taken came from class X students in Malang class X students. Data collection was carried out through observation, interviews, and questionnaires analyzed using qualitative and quantitative methods. The average total validation score from experts is 91.4%, which indicates that the Containing Culturally Responsive Teaching loaded microlearning module is very valid. The overall average product trial results reached 83.8% which is included in the valid category. The results of the Paired Sample t-test and Post test were 0.000 <0.05, so there is an effect of the microlearning module containing Containing Culturally Responsive Teaching on improving mathematical problem solving abilities and an increase in mathematical problem solving abilities before and after the use of the microlearning module containing Containing Culturally Responsive Teaching by looking at the average value of the pre-test 6.1694 and post-test 24.2788. So it can be concluded that the Containing Culturally Responsive Teaching loaded microlearning module has been successfully developed and validated so that it is suitable for use to improve mathematical problem solving abilities in the material of trigonometry comparisons in right triangles.